Dual Personality Model: Adjustment Indexes Towards an Integrative View of Personality Traits in a Highly-educated Argentinian Sample - Guadalupe de la IGLEASIA; Alejandro CASTRO SOLANO (European Journal of Mental Health, 2023)
Introduction: Differentiating between normal, pathological, and positive traits may be achieved by conceptualizing personality traits as a continuum in which these aspects could be placed as sickness or health poles. The tendency to focus on one aspect of the continuum to the detriment of the other has prompted the following question: What would be the outcome of studying both aspects conjointly? Aims: This study aimed at assessing the appropriateness of different personality adjustment indexes proposed by the Dual Personality Model. These indexes combine positive and pathological aspects of personality in a single measure. Methods: The sample was composed of 1061 individuals from the general Argentinian population (Mage=39.87, SD=14.68, 51% males). Results: Individuals who scored higher on the personality adjustment index (PAI) had higher positive traits and well-being, and lower pathological traits, psychological symptoms, and lack of personality functioning. Also, higher scores on each trait continuum index were related to favorable outcomes. Conclusions: It was concluded that PAI and trait continuum indexes are potentially useful measures for psychological research and for applied fields. The possibility of combining pathological and healthy aspects in a single measure makes it possible to view individuals in an integrated manner in any personality assessment. The indexes should be considered global measures which could be further complemented with a disaggregated analysis.